2021
DOI: 10.1530/erc-21-0198
|View full text |Cite
|
Sign up to set email alerts
|

Mammary carcinoma in aged gerbil mothers after endocrine disruption in pregnancy and lactation

Abstract: Compounds that trigger breast cancer onset and establishment are of great interest in biological research. Endocrine disruptors are relevant because they initiate carcinogenesis by changing endocrine pathways. Bisphenol A (BPA), as a ubiquitous xenoestrogen, is largely associated with dysfunctions in the female reproductive system and associated organs. This study proposes an investigation of the mammary gland (MG) in aged Mongolian gerbil (Meriones unguiculatus) mothers after their exposure to BPA in two wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…However, by the moment, they did not report as substantial changes associated with developmental programming or DOHaD [187]. Other studies performed in Mongolian gerbil (Meriones unguiculatus), in which mothers were exposed to bisphenol during pregnancy and lactation, showed that bisphenol causes adverse effects on mammary gland tissue, inducing the development of carcinoma through the increase in TGFβ and metalloproteinases MMP2, MMP3, and MMP9 expression, making it obvious the deleterious effects of bisphenol exposure [188]. In addition, Yousef MM.…”
Section: Industrialization Pregnancymentioning
confidence: 91%
“…However, by the moment, they did not report as substantial changes associated with developmental programming or DOHaD [187]. Other studies performed in Mongolian gerbil (Meriones unguiculatus), in which mothers were exposed to bisphenol during pregnancy and lactation, showed that bisphenol causes adverse effects on mammary gland tissue, inducing the development of carcinoma through the increase in TGFβ and metalloproteinases MMP2, MMP3, and MMP9 expression, making it obvious the deleterious effects of bisphenol exposure [188]. In addition, Yousef MM.…”
Section: Industrialization Pregnancymentioning
confidence: 91%
“…Rodent Bisphenols (BPA [139,227,[232][233][234] (also sensitizes to DMBA [233,[237][238][239]), BPS [117,229], BPAF [117]), PCBs [242] (also sensitize to DMBA and MNU [242]), TCDD sensitizes to DMBA [240], phthalate mixture sensitizes to MNU [129] BPA sensitizes to DMBA [238] Pharmaceutical hormones [138],…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Rodent studies also provide evidence that chemicals that alter MG development can also induce mammary tumors and/ or sensitize the MG to other chemical carcinogens. One example is BPA, which, as noted above, alters MG development in rodents with exposure during WoS [118,119,[227][228][229][230][231], and exposures during multiple WoS induce mammary hyperplasia and spontaneous mammary adenocarcinomas in rodents [139,227,[232][233][234][235]. BPA analogs such as BPS and BPAF have been reported to have similar developmental and tumorigenic outcomes [117,229].…”
Section: Experimental Studiesmentioning
confidence: 99%
See 2 more Smart Citations